A Cambrian fossil from the Chengjiang fauna sharing characteristics with gilled lobopodians, opabiniids and radiodonts - Liu, Jianni; Dunlop, Jason A.; Steiner, Michael; Shu, Degan (Frontiers in Earth Science, 2022)
Parvibellus atavus gen. et sp. nov. from the Early Cambrian Chengjiang fauna of China is a small fossil preserving a distinct cephalic region bearing a pair of lateral projections and a circular, ventral mouth. The trunk bears eleven pairs of flap-like appendages and a short pair of terminal projections. This character combination is unique for the Chengjiang biota. A circular ventral mouth is seen in Radiodonta and in some of the gilled lobopodians which are thought to be the radiodontan’s closest relatives. Parvibellus atavus, gilled lobopodians and radiodontans also share the character of flap-like appendages along the trunk. However, the new fossil differs from radiodontans and gilled lobopodians by its small size and the absence of enlarged and/or raptorial frontal appendages. It also differs from gilled lobopodians in lacking ventral lobopod limbs, and from radiodontans in lacking stalked eyes. It could, however, be part of an early radiation of nektonic lower stem-Euarthropoda; a grade of body plans from which the gilled lobopodians and radiodontans possibly arose.